1996
DOI: 10.1074/jbc.271.40.24967
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepatic Na,K-ATPase Activity during Hepatic Regeneration Is Associated with Induction of the β1-Subunit and Expression on the Bile Canalicular Domain

Abstract: Cellular and molecular mechanisms regulating the activity of the sodium pump or Na,K-ATPase during proliferation of hepatocytes following 70% liver resection have not been defined. Na,K-ATPase may be regulated by synthesis of its ␣-and ␤-subunits, by sorting to either the sinusoidal or apical plasma membrane domains, or by increasing membrane lipid fluidity. This study investigated the time course of changes during hepatic regeneration for Na,K-ATPase activity, lipid composition and fluidity, and protein conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Fluidization of the membrane increased Na,KATPase activity in the canalicular fraction in control rats (where ␤1 was absent), but not in that from rats undergoing regeneration (where ␤1 was present). Thus there appear to be functional differences in canalicular Na,K-ATPase depending on whether or not ␤1 is expressed there (8). We can now speculate that the missing ␤ subunit in normal adult rats is ␤3 and that it is responsible for the difference.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fluidization of the membrane increased Na,KATPase activity in the canalicular fraction in control rats (where ␤1 was absent), but not in that from rats undergoing regeneration (where ␤1 was present). Thus there appear to be functional differences in canalicular Na,K-ATPase depending on whether or not ␤1 is expressed there (8). We can now speculate that the missing ␤ subunit in normal adult rats is ␤3 and that it is responsible for the difference.…”
Section: Discussionmentioning
confidence: 92%
“…The polarized distribution of reactivity for ␤1 correlated with the prior histochemistry, suggesting that the presence of ␤1 makes the enzyme active. Most recently, this group reported that the increased ␤1 seen during hepatic regeneration was specifically localized to the canalicular domain and lateral surfaces of the hepatocyte (8). Fluidization of the membrane increased Na,KATPase activity in the canalicular fraction in control rats (where ␤1 was absent), but not in that from rats undergoing regeneration (where ␤1 was present).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, like the GABAergic system, changes in Na/K ATPase activity and in particular the ␣1 and perhaps ␤1 subunits have been described in association with changes in hepatocyte proliferative activity. [10][11][12][13][14] The objectives of this study were to (1) document PD levels in HCC and adjacent nontumor tissues, (2) describe the nature and extent of GABA receptor and Na/K ATPase expression in these tissues, and (3) determine what impact enhanced GABA A receptor expression has on malignant hepatocyte growth in vivo.…”
mentioning
confidence: 99%
“…These observations suggest that the enzyme may not traffic exclusively as ␣␤-heterodimers. Moreover, it has been shown that increases in a single subunit of the Na ϩ -K ϩ -ATPase not only occur but have also been implicated in increasing pump activity (33). Our observations would suggest that enzyme function may be increased by alteration in basolateral expression of ␣-subunit alone, which implies that there may be an excess of ␤-subunit already present in or near the membrane.…”
Section: Discussionmentioning
confidence: 61%